STUDI LITERATUR KEPEMIMPINAN WIRAUSAHA DALAM MENGHADAPI TANTANGAN GLOBAL - Safuan Safuan (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
The progressions have raises new standards and every organization is required to roll out improvements quick, right and adaptable, in light of the fact that generally the organization will be hard to contend all around later on. The ramifications of worldwide ecological change expects organization to change the methodology of the organization that initially situated to nearby all inclusive arranged, to the organization without bounds should dependably be inviting to future hierarchical changes keeping in mind the end goal to have the capacity to be leaders of progress later on. It takes entrepreneurial leadership to react to difficulties of worldwide change with the goal that the organization can adjust and still exist in zone of worldwide rivalry.